A Critical Discourse Analysis On Rhetorical Devices In “The King’s Speech” Movie - Mudhoffar Abdul Hadi; Elisa Nurul Laili (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This study aims to identify the rhetorical devices used by the character of King George VI in The King’s Speech (2010) and to explain how these devices operate within the microstructural level of discourse. The research is grounded in the understanding that rhetoric plays a crucial role in shaping persuasive political communication. George VI was selected as the research subject because of his distinctive linguistic style—authoritative, composed, and emotionally resonant—particularly after overcoming his earlier speech difficulties. The study employs a qualitative research design using the framework of Critical Discourse Analysis (CDA). The data consist of selected excerpts from George VI’s speeches obtained from the film and its transcript. Data collection involved repeated viewing of the film, reading the transcript, and extracting utterances containing rhetorical features. The analysis followed two stages: classifying rhetorical devices based on Jones and Peccei’s (2004) categories—pronouns, euphemism, metaphor, rule of three, and parallelism—and examining microstructures through Van Dijk’s theory. The findings reveal that George VI consistently uses rhetorical devices to construct ethos, evoke pathos, and reinforce logos. Pronouns such as we and our are deployed to build national unity, while parallelism and the rule of three strengthen rhythm, emphasis, and clarity. Microstructural analysis demonstrates that these devices work together to create a macrostructural theme centered on unity, moral resilience, and national preparedness during wartime. This study highlights that rhetorical devices in political speech are not merely stylistic choices; they function as ideological tools that shape public perception and reinforce collective identity.